Analisis Implementasi Kebijakan Gerakan Literasi Sekolah (GLS) Pada Jenjang Sekolah Dasar Di Kabupaten Malang - Minayugie, Apridhona Tito; Syahri, Mohammad (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: PISA (Program for International Student Assessment) states that literacy is an important ability to be mastered. Based on the 2019 PISA report, Indonesia is ranked 72 out of 78 countries for student reading skills. On one side of the school literacy movement (GLS) has been going on since 2016. This study aims to 1) describe the implementation of the GLS Elementary School level at SDN 2 and 3 PandansariNgantang District Malang Regency. 2) analyze the implementation of GLS policies and describe the supporting-inhibiting factors and efforts in their implementation. This research uses a descriptive qualitative approach. Data collection techniques are done using observation, interviews, and documents. Data analysis of the results of the study was carried out by data reduction, data presentation, and concluding (data verification). The results showed that 1) in general the implementation of GLS by structuring, using and utilizing library building facilities to support implementation. Supported by school residents such as school principals and teachers who have achievements at the national level of literacy. 2) The implementation of GLS has fulfilled 2 of 4 aspects, namely aspects of communication and resources. While the aspect that becomes an obstacle is the aspect of disposition and bureaucratic structure. The main constraints experienced in the implementation of GLS are the unavailability of librarians and the involvement of parents in the implementation of activities that are still lacking, and the School Literacy Team (TLS) has not been formed. Efforts to overcome obstacles in the implementation of GLS include involving students in the addition of literature, the appointment of teachers as library staff.Keywords: Implementation Analysis, Policy, School Literacy MovementÂ Abstrak: PISA (Programme for International Student Assessment) menyebutkan bahwa literasi menjadi kemampuan yang penting untuk dikuasi. Berdasarkan laporan PISA tahun 2019 Indonesia menempati peringkat 72 dari 78 negara untuk kemampuan membaca siswa. Disatu sisi gerakan leterasi sekolah (GLS) telah berlangsung sejak tahun 2016. Penelitian ini bertujuan untuk 1) mendeskripsikan pelaksanaan GLS jenjang Sekolah Dasar di SDN 2 dan 3 Pandansari Kecamatan Ngantang Kabupaten Malang.2) menganalisis implementasi kebijakan GLS dan mendeskripsikan faktor pendukung-penghambat serta upaya dalam implementasinya. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Teknik pengumpulan data dilakukan dengan menggunakan observasi, wawancara serta dokumen. Analisis data hasil penelitian dilakukan dengan reduksi data, penyajian data, dan penarikan kesimpulan (verifikasi data). Hasil penelitian menunjukkan bahwa 1) secara umum pelaksanaan GLS dengan penataan, penggunaan, dan pemanfaatan fasilitas gedung perpustakaan untuk menunjang implementasi. Didukung warga sekolah seperti kepala sekolah dan guru yang memiliki prestasi dibidanglieterasi tingkat nasional. 2) Pelaksanaan GLS telah memenuhi 2 dari 4 aspek, yaitu aspek komunikasi dan sumberdaya. Sedangkan aspek yang menjadi kendala adalah aspek disposisi dan struktur birokrasi. Kendala yang dialami dalam pelaksanaan GLS yang utama adalah belum tersedianya tenaga pustakawan serta keterlibatan orang tua dalam pelaksanaan kegiatan yang masih kurang, serta belum dibentuknya Tim Literasi Sekolah (TLS). Upaya mengatasi kendala dalam pelaksanaan GLS diantaranya melibatkan siswa dalam penambahan literatur, penunjukan guru sebagai tenaga perpustakaan.Kata kunci: Analisis Implementasi, Kebijakan, Gerakan Literasi Sekolah